Hubungan Daya Tahan Kardiovaskular dengan Kepercayaan Diri Siswa pada Kelas Olahraga - Nusantara R, Cahya; Maryati, Sri; Sudrazat, Adang; Ropi, Ucu Abdul (Universitas Galuh, 2023)
The purpose of this study was to determine the relationship between cardiovascular and self-confidence. This study used a correlation method using test and measurement techniques on independent variables, namely cardiovascular and dependent variables, namely self-confidence. The population used was SMA Negeri 3 Ciamis Regency The sample used amounted to 50 people. Discussion. Based on the results of the regression line linearity test shows that the number obtained is greater than 0.05, it is proven that for cardiovascular independent variables with confidence is 0.971 > 0.05 meaning that cardiovascular variables do not affect self-confidence variables. Based on the results of the correlation test between the independent variable, namely cardiovascular and bound variables, namely self-confidence, a significance value of 0.953 greater than 0.05 means that cardiovascular and self-confidence are not related. Based on the results of the discussion starting from the calculation and analysis of the data that has been described, the author states that